Moving from traditional curriculum to primary years program (PYP) - Nahouli, Fadia A (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2006)
The pressure created by dynamic society has intensified the need for educational changes. This case study examines the nature of curriculum change as experienced by the Primary Years Program (PYP) coordinator, preschool coordinator, and two KGII classroom teachers in one private school in Lebanon. The study sheds light on the difficulties and challenges facing educators when they engage in curricular change. Data for this study was collected from interviews, observations, and documents. Findings show that pre-service and in-service programs and group work helped coordinators and teachers in implementing the changes. Data also shows that the staff faced difficulties in the implementation of the program due to lack of time. Grouping of children into centers, gaining parents' support, ineffectiveness of some of the in-service programs, and limited resources further hindered the implementation. Although most of the teachers were not involved in the decision of adopting the new program, interviews and observations reveal that teachers seem to have positive attitudes towards the change and appear to accept the reform requirements. Change needs to be seen as a natural part of the learning process and of teacher s and principal's professional growth.
: Mémoire
Keywords: Curricula; Curriculum; Cycle primaire; Elementary Education